(untitled) (Third Sector Social Economic Review, 2022)
This study was conducted to determine the loneliness levels felt by healthcare professionals in virtual environments. It was obtained through the formula to be asked using the literature. The question formula consists of demographic questions and a tested Virtual Environment Loneliness Scale (SLS) question by Korkmaz in 2014. The total mean score of the Virtual Loneliness Scale was measured as 2.22±0.23. The mean score in the virtual general sub-dimension was calculated as 2.48±0.63, and the mean score in the Virtual Sharing sub-dimension was calculated as 1.56±0.64 in the Social Loneliness sub-dimension 2.75±0.84. The Cronbach alpha internal consistency coefficients of the scale were calculated as 0.60 for the virtual socialization dimension, 0.87 for the virtual sharing dimension and 0.73 for the virtual loneliness dimension. The findings obtained as a result of the research show that the virtual loneliness levels of healthcare professionals are at an average level, and the virtual sharing is quite low. Although the sharing in virtual environments is low (1.56±0.64), it was found that virtual socialization (2.48±0.63) and loneliness in these environments (2.75±0.84) are higher. When gender is considered as the introductory feature of healthcare professionals, the virtual loneliness scale of men mean total score (2.13±0.42) was higher than female (2.35±0.51). There was no statistically significant difference between the mean scores of virtual socialization and virtual loneliness sub-dimensions and demographic indicators (p>0.05).